Conduction block in immune‐mediated neuropathy: paranodopathy versus axonopathy. (26th April 2019) - Garg, N.; Park, S. B.; Howells, J.; Vucic, S.; Yiannikas, C.; Mathey, E. K.; Nguyen, T.; Noto, Y.; Barnett, M. H.; Krishnan, A. V.; Spies, J.; Bostock, H.; et al.
Abstract : Background and purpose: Conduction block is a pathognomonic feature of immune‐mediated neuropathies. The aim of this study was to advance understanding of pathophysiology and conduction block in chronic inflammatory demyelinating polyneuropathy (CIDP) and multifocal motor neuropathy (MMN). Methods: A multimodal approach was used, incorporating clinical phenotyping, neurophysiology, immunohistochemistry and structural assessments. Results: Of 49 CIDP and 14 MMN patients, 25% and 79% had median nerve forearm block, respectively. Clinical scores were similar in CIDP patients with and without block. CIDP patients with median nerve block demonstrated markedly elevated thresholds and greater threshold changes in threshold electrotonus, whilst those without did not differ from healthy controls in electrotonus parameters. In contrast, MMN patients exhibited marked increases in superexcitability. Nerve size was similar in both CIDP groups at the site of axonal excitability. However, CIDP patients with block demonstrated more frequent paranodal serum binding to teased rat nerve fibres. In keeping with these findings, mathematical modelling of nerve excitability recordings in CIDP patients with block support the role of paranodal dysfunction and enhanced leakage of current between the node and internode. In contrast, changes in MMN probably resulted from a reduction in ion channel density along axons. Conclusions: The underlying pathologies in CIDP and MMN are distinct. Conduction block in CIDP is associated with paranodal dysfunction which may be antibody‐mediated in a subset of patients. In contrast, MMN is characterized by channel dysfunction downstream from the site of block.